2019
DOI: 10.21608/ejnf.2019.79415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition of Anise, Clove and Thyme Essential Oils on Barki Lambs Performance, Digestibility, Rumen Fermentation, Carcass Characteristics and Intramuscular Fatty Acids

Abstract: ecently, some plants essential oils (EO) are used as natural feed additives for ruminants because their major bioactive compounds have antimicrobial properties that can be effective against undesirable rumen microbes. In addition, EO have not an adverse effect either on animal or human health and environment. This work was carried out to evaluate the effect of natural additives as essential oils addition on animal performance, feed intake, apparent digestibility, carcass characteristics, chemical composition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
2
10
1
Order By: Relevance
“…Therefore, mixing it reduces the sheep's feed intake. These findings are in conflict with the literature data [35,[37][38][39] about no effect on feed intake of sheep when these medicinal plants are used alone.…”
Section: Feed Intake and Nutrient Digestibilitycontrasting
confidence: 99%
See 2 more Smart Citations
“…Therefore, mixing it reduces the sheep's feed intake. These findings are in conflict with the literature data [35,[37][38][39] about no effect on feed intake of sheep when these medicinal plants are used alone.…”
Section: Feed Intake and Nutrient Digestibilitycontrasting
confidence: 99%
“…The addition of RTPM and LPCM supplementation did not affect significantly the nutrient digestibilities and nutritive value. These results are consistent with [7,33,35,36,46,47,48] when each herb is used alone. While [2,41,42] indicated a significant improvement in the nutrient digestibility and nutritive value when using some medicinal plants alone.…”
Section: Feed Intake and Nutrient Digestibilitysupporting
confidence: 81%
See 1 more Smart Citation
“…Serum HDL level was numerically decreased in groups fed NSO as compared to the control animals. This result is in concord with that revealed by (El-Essawy et al, 2019a and2019b), who noted that plasma levels of HDL were not influenced by the addition of EO to the diet in Barki lambs and ewes; however, El-Hawy et al, (2018) noticed that feeding ration containing Nigella sativa meal in Barki ewes led to a significant lessen in HDL level comparing to control. There was a trend (P=0.07) in LDL concentration to be higher in lambs fed on T2 (21.43 mg dl 1 ) compared to the control.…”
Section: Blood Metabolitessupporting
confidence: 80%
“…The effects of using thyme EO as an additive to alter the fermentation of alfalfa silage in ruminants by in vitro methods showed that thyme EO reduced the amount of gas produced compared with the treatment without additives (Pour et al, 2017;El-Essawy et al, 2019). Effect of EO and AP on GP is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%